Reconstruction of soft tissue defects in Fournier’s gangrene at a tertiary care centre - Saleem, Abid; Mohsin, Mir; Zargar, Haroon Rashid; Baba, Peerzada Umar Farooq; Wani, Adil Hafeez; Zaroo, Mohammad Inam; Bashir, Sheikh Adil; Rasool, Altaf; Bijli, Akram Hussain; Bhat, Tanveer Ahmed; Mir, Farooq Ahmed; Bhat, Mushtaq Ahmed (International Journal of Research in Medical Sciences, 2016)
Background: Fournier’s gangrene is an acute and potentially lethal multi-bacterial necrotizing infection that primarily involves the scrotum but may extend beyond its confines to perineum and abdominal wall. The disease may result in sepsis and death if treatment is delayed. Management consists of timely diagnosis, aggressive debridement, broad-spectrum antibiotics followed by reconstruction which still remains a surgical challenge. Methods: It is a prospective study conducted from Jan 2006 to Dec 2015 on 29 patients of Fournier’s gangrene who were referred to the department of Plastic and Reconstructive Surgery, Sheri-Kashmir Institute of Medical Sciences, Srinagar, Kashmir, for reconstruction after initial debridement by general surgeon/urologist. The patient’s age, predisposing factors, site and the size of the defects, reconstructive options used and outcome were evaluated. Assessment of testicular function was done at 6 months by sperm count and morphology. Results: A total of 29 patients of Fournier’s gangrene consisting of 28 males and one female were included in the study. The mean age was 37 years and the most common comorbidity was diabetes mellitus in 18 patients (62%). Wounds were allowed to heal by secondary intension in 8 patients. Scrotal advancement flap was done in seven patients. Split thickness skin grafting (STSG) of extensive wounds was done in 11 patients and testes were placed in medial thigh subcutaneous pocket in one patient. Two elderly diabetic patients succumbed to sepsis and multi organ failure. Overall complication rate was 18.5%. Conclusions: Thorough debridement and early wound cover are essential in the management of Fournier’s gangrene for successful rehabilitation. Various reconstructive options are available with no conclusive evidence to support flap rather than skin graft and most of the procedures result in preservation of testicular function in the long term.